Low-/Negative-Pressure Hydrocephalus: To Understand the Formation Mechanism from the Perspective of Clinicians - Li, Guangzhao; Lin, Bin; Yang, Fei (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Low-/negative-pressure hydrocephalus (LPH/NePH) is uncommon in clinical practice, and doctors are unfamiliar with it. LPH/NePH is frequently caused by other central nervous system diseases, and patients are frequently misdiagnosed with other types of hydrocephalus, resulting in delayed treatment. LPH/NePH therapy evolved to therapeutic measures based on “external ventricular drainage below atmospheric pressure” as the number of patients with LPH/NePH described in the literature has increased. However, the mechanism of LPH/NePH formation is unknown. Thus, understanding the process of LPH/NePH development is the most important step in improving diagnosis and treatment capability. Based on case reports of LPH/NePH, we reviewed theories of transcortical pressure difference, excessive cerebral venous drainage, brain viscoelastic changes, and porous elastic sponges.
Keywords: low-pressure hydrocephalus; negative-pressure hydrocephalus; cerebral viscoelasticity change theory; excessive drainage of cerebral veins theory; porous elastic sponge theory